(untitled) (Architecture Image Studies, 2026)
This study examines the direct and indirect effects of Work-Life Balance (WLB) and Work-Family Conflict (WFC) on the performance of permanent lecturers at private universities in Tual City, Maluku Province, Indonesia, with Organizational Commitment as a mediating variable. A quantitative approach was employed using questionnaires distributed to permanent lecturers, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The results reveal that WLB has a positive and significant effect on lecturer performance (β = 0.304; p = 0.012) and Organizational Commitment (β = 0.655; p = 0.000). WFC significantly influences Organizational Commitment (β = 0.297; p = 0.000) but does not have a direct effect on performance (β = 0.064; p = 0.535). Organizational Commitment fully mediates the relationship between WFC and performance (β = 0.155; p = 0.001) and partially mediates the relationship between WLB and performance (β = 0.343; p = 0.001). These findings suggest that university management should enhance WLB through flexible work arrangements and wellness programs, while reducing WFC through family-supportive initiatives such as counseling. Strengthening organizational commitment via recognition, rewards, and career development opportunities is essential to improving lecturer performance. This study contributes to the literature by highlighting the mediating role of Organizational Commitment in the underexplored context of private higher education in Eastern Indonesia, offering insights into how work-related factors shape academic performance.